2008
DOI: 10.1164/rccm.200703-418oc
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome mRNA Expression in Human Monocytes during Early Septic Shock

Abstract: Rationale: Monocytes are central to the initiation of the inflammatory response in sepsis, with caspase-1 activation playing a key role. Monocyte deactivation during sepsis has been linked to poor outcomes. Objectives: Given the importance of caspase-1 in the immune response, we investigated whether monocytes from patients early in septic shock demonstrate alterations in mRNAs for caspase-1-related molecules. Methods: Patients with septic shock (n 5 26; age .18 years), critically ill intensive care unit patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 33 publications
(33 reference statements)
6
67
0
2
Order By: Relevance
“…In agreement with our findings, Rowe and colleagues and Fahy and colleagues observed delayed apoptosis in neutrophils isolated from LPStreated Casp1 2/2 mice with a transitional inflammatory response (46,47). The authors concluded that caspase-1 was not required for IL-1b activation but likely modulated lung inflammation via IL-18.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with our findings, Rowe and colleagues and Fahy and colleagues observed delayed apoptosis in neutrophils isolated from LPStreated Casp1 2/2 mice with a transitional inflammatory response (46,47). The authors concluded that caspase-1 was not required for IL-1b activation but likely modulated lung inflammation via IL-18.…”
Section: Discussionsupporting
confidence: 91%
“…In conclusion, inflammasomes are critical regulators of the innate and adaptive immune system that connect cell death and inflammatory pathways (7,9,47). Here, we have found that the inflammasome pathway dependent on caspase-1 is activated in critically ill patients and, furthermore, that increases in circulating IL-18 correlate with disease severity and mortality in the MICU.…”
Section: Discussionmentioning
confidence: 74%
“…15596-026) and then converted to cDNA. Gene expression was calculated as relative copy numbers, as described previously (30,33). Briefly, C t values of the p62 gene were subtracted from the average Ct of two housekeeping genes (GADPH and CAP1), and the resulting ⌬C t was used in the following equation: RCN ϭ (2 Ϫ⌬Ct ) 100.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, C t values of the p62 gene were subtracted from the average Ct of two housekeeping genes (GADPH and CAP1), and the resulting ⌬C t was used in the following equation: RCN ϭ (2 Ϫ⌬Ct ) 100. The relative copy number of a gene is represented as the number of copies relative to the 100 copies of average housekeeping genes (30,33).…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative PCR was done in the StepOne Plus machine using SYBR Green PCR mix (Applied Biosystems). The values of target genes were normalized to the values of two housekeeping genes, GAPDH and CAP-1, and expressed as relative copy number, as described previously (52)(53)(54).…”
Section: Real-time Pcrmentioning
confidence: 99%